2018
DOI: 10.1002/jcb.26830
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of LncRNA‐MIR31HG regulates cell migration and proliferation by affecting miR‐31 and miR‐31* in Hirschsprung's disease

Abstract: Hirschsprung's disease (HSCR) is a birth defect that causes a failure of the enteric nervous system to cover the distal gut during early embryonic development. Evidence shows that long non-coding RNAs (lncRNA) play important roles in HSCR. The MIR31 host gene (MIR31HG), also known as Loc554202, is a long non-coding RNA (lncRNA), which acts as the host gene of (microRNA) miR-31 and miR-31*. There have been no studies regarding its function in early developmental defects during pregnancy, and its downstream gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…For example, lncRNA MIR100HG -derived miR-100 and miR-125b have been shown to participate in the resistance of colorectal cancer to cetuximab through Wnt/β-catenin signaling (15). MIR31HG , the host gene of miR-31 , has been shown to contribute to the pathogenesis of Hirschsprung’s disease through the MIR31HG - miR-31/31* - ITIH5 / PIK3CG pathway (16). MIR155HG -derived miR-155-5p and miR-155-3p have been shown to suppress the transcription and translation of protocadherin ( PCDH )9 and PCDH7 , thereby promoting glioma cell migration and invasion (17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNA MIR100HG -derived miR-100 and miR-125b have been shown to participate in the resistance of colorectal cancer to cetuximab through Wnt/β-catenin signaling (15). MIR31HG , the host gene of miR-31 , has been shown to contribute to the pathogenesis of Hirschsprung’s disease through the MIR31HG - miR-31/31* - ITIH5 / PIK3CG pathway (16). MIR155HG -derived miR-155-5p and miR-155-3p have been shown to suppress the transcription and translation of protocadherin ( PCDH )9 and PCDH7 , thereby promoting glioma cell migration and invasion (17).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of enteric neurons, the patients suffer from abdominal enlargement and constipation, which even threaten their lives. Until now, several lncRNAs have been reported to be abnormally expressed in colon tissues of HSCR patients, which play an important regulatory role in the progression of HSCR ( 19 , 20 ). In this study, DRAIC was found to be highly expressed in colon tissues of HSCR patients, which was consistent with the results reported in a previous article ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence suggests a relationship between lncRNAs and HSCR, all based on the comparative expression assays of specific lncRNAs in bowel tissue from HSCR patients and controls [73][74][75][76][77][78]. In our study we have performed a differential qRT-PCR assay in the EPCs from HSCR patients and controls, which has allowed us to identify new lncRNAs as potential regulatory elements implicated in ENS development and HSCR onset.…”
Section: Discussionmentioning
confidence: 99%